Chert quarries and workshops in the Humid Pampa sub-region: New contributions on exploitation techniques and circulation through study of chaînes opératoires - Barros, Maria Paula (2015)
The study of technological organization associated with hunter-gatherers groups has been one of the topics of greatest interest in the archaeological research of the Pampean region. In this sense, the aims of this paper were to interpret the role of the Cerro Largo Formation chert in the technological practices of human groups and to discuss how this rock was used and transported in the center of the Humid Pampa sub-region during the Late Holocene. We will present the techno-morphological analysis on chert artifacts recovered from Boca de la Sierra workshop in order to identify how this stone was used at the beginning of its exploitation. Then, we will compare and discuss diverse chaînes opérotoires on chert found in archaeological sites located at different distances from the sources. In Boca de la Sierra workshop, we recorded three initial forms of exploitation of the nodules. The Cerro Largo Formation chert had been transported from this workshop to other sites in the form of different kinds of partially and/or totally decorticated cores, nodules, large flakes, and possibly tools. In those sites located at a short distance from the quarry workshops (Empalme Querandíes 1 and Laguna La Barrancosa 2) we observed complete chaînes opérotoires organized through débitage, with low production of standardized blank and a high frequency of external flakes used as blank for the manufacture of different kinds of tools. In those sites located at a long distance from the quarry workshops (Laguna La Larga and Laguna Seca 2), we recorded chaînes opérotoires developed almost entirely. Even though some expedient tools are recorded, the greatest maximization in the use of Cerro Largo Formation chert is remarkable. The high proportion of standardized, small and shaped tools, the identification of exhausted cores, the use of a bipolar technique, and the presence of resharpening flake edges show a curated technological strategy. Finally, the presence of complete chaînes opérotoires close to the hills allow us to infer direct access to the outcrops and an easy acquisition of chert; whereas the features observed in the other sites indicate that the chert acquisition was done by specific trips or by social exchange and interaction networks with other groups.